P144 The uncommon meets the common: Invasive Aspergillosis and tuberculosis co-infection in non-neutropenic patients— arare association. (20th September 2022) - R, Akshatha; Bohra, Gopal Krishna; Shankar, Durga; Kumar, Deepak; Midha, Naresh Kumar; Jain, Vidhi; Sharma, Shivang; N, Santhanam; Garg, Mahendra Kumar; Singh, Kuldeep; Chauhan, Nishant Kumar; Sharma, Ankur
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: Background and Objective: Invasive aspergillosis (IA) is known to occur in immunocompromised patients including neutropenic patients. But, recently increasing cases have been reported in patients with non-classical risk factors and non-neutropenic patients like diabetes mellitus, chronic lung disease, HIV infection, critically ill patients, etc. According to ISHAM these non-classical risk factors should be included in EORTC/MSG host criteria for diagnosis of invasive aspergillosis. India has a high tuberculosis (TB) burden, and this is always considered as the first differential for any patient with fever, cough, hemoptysis, and weight loss. Post-tubercular chronic pulmonary aspergillosis common reported condition. However, co-infection of active TB and invasive aspergillosis is less reported. This co-infection could be one of the contributors of high morbidity and mortality in cases with tuberculosis. We hereby present a series of five cases of TB concomitant with invasive aspergillosis in non-neutropenic patients. Methods: This is a prospective observational study, all patients admitted with molecular diagnosis (GeneXpert) of tuberculosis and with at least one non-classical risk factor for invasive aspergillosis were subjected to further evaluation. Diagnosis of invasive aspergillosis was considered in patients who had at least one clinical and one mycological EORTC criteria. Galactomannan level in different samples was measured via Platelia TM ELISA. The efficacy of different antifungals and outcomes were analyzed. Results: Total 57 patients with TB underwent for evaluation of invasive aspergillosis. Among them, five patients were diagnosed to have concomitant TB and invasive aspergillosis, of which three cases of CNS TB and CNS aspergillosis and two had concomitant pulmonary infections. The average age was 31 ± 12 years with a female preponderance (4/5). Two patients were HIV positive, while among non-HIV patients, one had CD4 cytopenia (CD4-171). One patient had no known predisposing factor. Radiologically, most common pulmonary lesions were patchy consolidation with centrilobular nodules with tree in bud appearance, while CNS lesions showed multiple ring-enhancing lesions. All the patients had CBNAAT positive, two from BAL sample, 1 from CSF, and 1 from the lymph node. Rifampicin was sensitive in all, except one who had rifampicin resistance indeterminate. Of these patients, four were probable invasive aspergillosis satisfying the host, mycological and clinical factors as per the EORTC/MSGERC 2021 guidelines. The treatment of coinfection is challenging due to the interaction of rifampicin with voriconazole, which is the drug of choice for invasive aspergillosis. Here, 3 patients were treated with Inj amphotericin B, while the other 2 patients were started on voriconazole with rifampicin sparing regimen for TB. Of the 5 patients, 4 patients survived with excellent response to the treatment, with one fatality. Conclusion: The possibility of concurrent TB and invasive aspergillosis in non-neutropenic hosts should be considered to avoid devastating outcomes. The lack of clinical suspicion may result in misdiagnosis, and most importantly, the chronicity of the infection makes it indistinguishable from TB. Moreover, the co-administration of antifungal and anti-TB medications presents significant therapeutic challenges necessitating thorough evaluation and monitoring.